Gut microbiota from sigma-1 receptor knockout mice induces depression-like behaviors and modulates the cAMP/CREB/BDNF signaling pathway - Li, Jia-Hao; Liu, Jia-Li; Li, Xiu-Wen; Liu, Yi; Yang, Jian-Zheng; Chen, Li-Jian; Zhang, Kai-Kai; Xie, Xiao-Li; Wang, Qi (Frontiers in Microbiology, 2023)
Introduction Depression is a common mental disorder that affects approximately 350 million people worldwide. Much remains unknown about the molecular mechanisms underlying this complex disorder. Sigma-1 receptor (Sig-1R) is expressed at high levels in the central nervous system. Increasing evidence has demonstrated a close association between the Sig-1R and depression. Recently, research has suggested that the gut microbiota may play a crucial role in the development of depression. Methods Male Sig-1R knockout (Sig-1R KO) and wild-type (WT) mice were used for this study. All transgenic mice were of a pure C57BL/6J background. Mice received a daily gavage of vancomycin (100 mg/kg), neomycin sulfate (200 mg/kg), metronidazole (200 mg/kg), and ampicillin (200 mg/kg) for one week to deplete gut microbiota. Fecal microbiota transplantation (FMT) was conducted to assess the effects of gut microbiota. Depression-like behaviors was evaluated by tail suspension test (TST), forced swimming test (FST) and sucrose preference test (SPT). Gut microbiota was analyzed by 16s rRNA and hippocampal transcriptome changes were assessed by RNA-seq. Results We found that Sig-1R knockout induced depression-like behaviors in mice, including a significant reduction in immobility time and an increase in latency to immobility in the FST and TST, which was reversed upon clearance of gut microbiota with antibiotic treatment. Sig-1R knockout significantly altered the composition of the gut microbiota. At the genus level, the abundance of Alistipes, Alloprevotella, and Lleibacterium decreased significantly. Gut microbiota dysfunction and depression-like phenotypes in Sig-1R knockout mice could be reproduced through FMT experiments. Additionally, hippocampal RNA sequencing identified multiple KEGG pathways that are associated with depression. We also discovered that the cAMP/CREB/BDNF signaling pathway is inhibited in the Sig-1R KO group along with lower expression of neurotrophic factors including CTNF, TGF-α and NGF. Fecal bacteria transplantation from Sig-1R KO mice also inhibited cAMP/CREB/BDNF signaling pathway. Discussion In our study, we found that the gut-brain axis may be a potential mechanism through which Sig-1R regulates depression-like behaviors. Our study provides new insights into the mechanisms by which Sig-1R regulates depression and further supports the concept of the gut-brain axis.